Reproductive Success Rate and Blood Urea Nitrogen Status of Garut Ewes Fed Sorghum-Indigofera in Majalengka District - West Java - Rachmat Somanjaya; Aaf Falahudin; Fitra Aji Pamungkas (Buletin Peternakan, 2023)
The body's Blood Urea Nitrogen (BUN) concentration could be used as diagnostic information for interpreting animal nutritional status, improving nutritional management, and preventing metabolic disorders in ewes during the reproductive phase. This study aimed to evaluate the reproductive success rate and changes in the BUN status of Garut ewes fed sorghum-Indigofera in Majalengka District – West Java, Indonesia. Twenty-eight multiparous Garut ewes with an average body weight of 30 kg, aged 2-3 years or parity from 3rd to 4th, and non-pregnant were separated into two feed treatment groups; divided field grass (FG) and sorghum-Indigofera (SI) mixed feed. This study was designed using a Complete Randomized Design (CRD). After one month of feed acclimatization, all ewes were served an estrus synchronization protocol and mated naturally. A pregnancy test was carried out on the 28th day after mating using ultrasonography (USG). Seven blood samples were taken (1 time in the pre-mating phase and three times each in the pregnancy and lactation phases), and the BUN parameter was analyzed. The results showed that SI feed increased the number of ewes pregnant and giving birth compared to FG (10 vs. 9 and 9 vs. 6, respectively). Meanwhile, the average value of the BUN content of ewes in both FG and SI treatments during the premating, pregnancy, and lactation phases did not show any differences (p>0.05). The concentration of BUN is still in normal condition even though it has decreased from pre-mating until the lactation phase. It can be concluded that Sorghum-Indigofera mixed feed could increase reproductive success. However, the average value of BUN in the two types of feed treatment experienced the same status change in all reproductive phases. Both can overcome the energy deficit problem if they have sufficient feed.